2021
DOI: 10.1007/s10637-021-01155-w
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of weekly nab-paclitaxel plus carboplatin and concurrent thoracic radiotherapy in elderly patients with unresectable locally advanced non-small cell lung cancer

Abstract: Few clinical studies have been designed for elderly patients with locally advanced non-small cell lung cancer (NSCLC). We conducted a phase I study to evaluate the tolerability of carboplatin/nab-paclitaxel and concurrent thoracic radiotherapy in elderly patients with locally advanced NSCLC. The eligibility criteria were: unresectable stage III NSCLC, performance status 0 or 1, and age ≥75 years. Eligible patients received 6 weeks of weekly carboplatin/nab-paclitaxel and concurrent thoracic radiotherapy with a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(11 reference statements)
0
0
0
Order By: Relevance
“…Focusing on elderly patients, Omori et al reported a phase I study of this regimen. They showed that 30 mg/m 2 of nab-PTX is recommended for elderly patients and that this regimen is tolerable and effective for elderly, with an ORR of 76.5% (11). Biweekly administrational has also been reported (12).…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on elderly patients, Omori et al reported a phase I study of this regimen. They showed that 30 mg/m 2 of nab-PTX is recommended for elderly patients and that this regimen is tolerable and effective for elderly, with an ORR of 76.5% (11). Biweekly administrational has also been reported (12).…”
Section: Discussionmentioning
confidence: 99%